Traditional Chinese medicine Ze-Qi-Tang formula reduces inflammation in mice with asthma by inhibiting PI3K/AKT/NF-κB signaling pathway: ZQT improves asthma via PI3K/AKT/NF-κB pathway - Luo, He; Lin, Yuhong; Guan, Yuxin (Cellular and Molecular Biology, 2024)
Asthma is a chronic airway inflammatory disease. The excessive proliferation of airway smooth muscle cells (ASMCs) is associated with airway remodeling. Ze-Qi-Tang (ZQT) is a popular traditional Chinese medicine preparation and has been confirmed to have therapeutic effects on lung diseases. This study is aimed to probe the biological function of ZQT in asthma. RT-qPCR and ELISA were utilized for testing the mRNA levels and concentrations of pro-inflammatory factors. Colony formation and transwell assay were applied to test cell viability and migration. The mouse model with asthma was established by ovalbumin (OVA) induction. Western blot was utilized for detecting the activation of PI3K/AKT/NF-κB pathway. We found that the concentrations of proinflammatory factors in cells induced by PDGF-BB could been suppressed by ZQT. ZQT-H treatment notably repressed cell viability and proliferation. Furthermore, we proved the suppressive effect of ZQT on airway inflammation in asthma mice. Additionally, we discovered that ZQT could suppress the PI3K/AKT/NF-κB pathway in PDGF-BB-induced ASMCs. To sum up, ZQT reduced airway inflammation and remodeling in mice with asthma via inactivating PI3K/AKT/NF-κB pathway.